IMPROVEMENT OF POETIC CONTENT IN UZBEK CHILDREN'S POETRY TASHKENT STATE UNIVERSITY OF UZBEK LANGUAGE AND LITERATURE - Juraeva Gulnoza Akhmatovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyzes humorous works of children's poetry, created during the years of independence, from the point of view of poetic and meaningful harmony. The article analyzes children's literature, in particular, the poetry of D. Rajab, H. Imonberdiev, T. Adashbaev. During the years of independence, reflections on poetic innovations began to appear in children's poetry.